Highly regioselective isomerizing hydroformylation of long-chain internal olefins catalyzed by a rhodium bis(phosphite) complex - Pandey, Swechchha; Chikkali, Samir H. (ChemCatChem, 2015)
The single-step synthesis, coordination behavior, and application of a bis(phosphite) ligand in the isomerizing hydroformylation of internal olefins was investigated. Interestingly, high-pressure NMR spectroscopy investigations revealed unexpected inequivalency of the two phosphorus nuclei, which display bisequatorial coordination of the bis(phosphite) ligand in a trigonal bipyramidal rhodium complex. Upon employment in the isomerizing hydroformylation of the exceedingly challenging plant oil derived substrate methyl oleate, the bis(phosphite) rhodium complex revealed an unprecedented linear selectivity of 75%.
Keywords: alkenes; bis(phosphite)s; Hydroformylation; isomerization; Rhodium

Isomerizing hydroformylation of cashew nut shell liquid - Pandey, Swechchha; Shinde, Dinesh R.; Chikkali, Samir H. (ChemCatChem, 2017)
A small library of bisphosphorus ligands was evaluated in the rhodium-catalyzed isomerizing hydroformylation (I-HF) of cashew nut shell liquid (CNSL). The rhodium complex of 1,2-bis((di-tert-butylphosphanyl)methyl)benzene (BDTBPMB; L4) outperformed the other bisphosphite and bisphosphine ligands and unveiled a moderate selectivity of 28% and 50% in the I-HF of CNSL monoene and methoxy-protected monoene, respectively. The resultant aldehyde 16-(3-methoxyphenyl)hexadecanal P1 was isolated and its identity was fully established. Application of bis-phosphine ligand L4 in the I-HF of highly challenging CNSL cardanol (S3) and methoxy-protected CNSL cardanol yielded a linear selectivity of 74%, although with reduced conversion. To demonstrate the synthetic utility of our strategy, the obtained aldehyde (derived from S3) was subjected to hydrogenation and the resultant 3-(16-hydroxyhexadecyl) phenol (P8) was isolated in 89% isolated yield. High-pressure NMR investigation revealed selective formation of a bis-equatorial BDTBPMB-rhodium complex, which might be responsible for the excellent linear selectivity.

Synthesis of meta-substituted monodentate phosphinite ligands and implication in hydroformylation - Deshmukh, Satej S.; Gaikwad, Shahaji R.; Pandey, Swechchha; Mali, Pramod S.; Chikkali, Samir H. (Journal of Chemical Sciences, 2017)
Synthesis of meta-substituted phosphinite ligands 3,3'-(methoxyphosphanediyl) bis(N, N-diethylaniline) (4a) and methoxybis(3-methoxyphenyl) phosphane (4b), in high yields, has been demonstrated. Typical phosphorus chemical shift between 110-120 ppm, appearance of methoxy protons and corresponding carbon, as well as ESI-MS spectra unambiguously confirmed the existence of phosphinite ligands 4a and 4b. To demonstrate the synthetic usefulness of 4a and 4b, these ligands were tested in the rhodium catalyzed hydroformylation of 1-octene. The diethylamine substituted ligand 4a was found to be highly active, whereas 4bwas less reactive but revealed slightly better regioselectivity of 62% under optimized conditions. Additionally, 4a and 4b were found to catalyze the hydroformylation of styrene, 1-undecenol and 1,1-disubstituted functional olefin, methyl methacrylate. Both the ligands displayed excellent conversion of styrene, and 4b revealed an excellent branch selectivity of 75%. Although 1-undecenol proved to be amenable to hydroformylation (85-90% conversion to aldehyde), both the ligands failed to discriminate between the linear and branched products. Substrate methyl methacrylate proved to be highly challenging and reduced conversion (between 33-42%) was observed under optimized conditions. Ligand 4a was found to be highly selective towards linear aldehyde (81% linear selectivity).

Imido-P(V) trianion supported enantiopure neutral tetrahedral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Paithankar, Harshad; Chugh, Jeetender; Steiner, Alexander; Boomishankar, Ramamoorthy (Chemical Communications, 2018)
Charge-neutral chiral hosts are attractive due to their ability to recognize a wide range of guest functionalities and support enantio-selective processes. However, reports on such charge-neutral cages are very scarce in the literature. Here, we report an enantiomeric pair of tetrahedral Pd(II) cages built from chiral tris(imido) phosphate trianions and oxalate linkers, which exhibit enantioselective separation capabilities for epichlorohydrin, beta-butyrolactone, and 3-methyl- and 3-ethyl cyclopentanone.

Iron Catalyzed Hydroformylation of Alkenes under Mild Conditions: Evidence of an Fe(II) Catalyzed Process - Pandey, Swechchha; Raj, K. Vipin; Shinde, Dinesh R.; Vanka, Kumar; Kashyap, Varchaswal; Kurungot, Sreekumar; Vinod, C. P.; Chikkali, Samir H. (Journal of the American Chemical Society, 2018)
Earth abundant, first row transition metals offer a cheap and sustainable alternative to the rare and precious metals. However, utilization of first row metals in catalysis requires harsh reaction conditions, suffers from limited activity, and fails to tolerate functional groups. Reported here is a highly efficient iron catalyzed hydroformylation of alkenes under mild conditions. This protocol operates at 10-30 bar syngas pressure below 100 degrees C, utilizes readily available ligands, and applies to an array of olefins. Thus, the iron precursor [HFe(CO)(4)](-)[Ph3PNPPh3](+) (1) in the presence of triphenyl phosphine catalyzes the hydroformylation of 1-hexene (S2), 1-octene (S1), 1-decene (S3), 1-dodecene (S4), 1-octadecene (S5), trimethoxy(vinyl)silane (S6), trimethyl(vinyl)silane (S7), cardanol (S8), 2,3-dihydrofuran (S9), allyl malonic acid (S10), styrene (S11), 4-methylstyrene (S12), 4-iBu-styrene (S13), 4-tBu-styrene (S14), 4-methoxy styrene (S15), 4-acetoxy styrene (S16), 4-bromo styrene (S17), 4-chloro styrene (S18), 4-vinylbenzonitrile (S19), 4-vinylbenzoic acid (S20), and allyl benzene (S21) to corresponding aldehydes in good to excellent yields. Both electron donating and electron withdrawing substituents could be tolerated and excellent conversions were obtained for S11-S20. Remarkably, the addition of 1 mol % acetic acid promotes the reaction to completion within 16-24 h. Detailed mechanistic investigations revealed in situ formation of an iron-dihydride complex [H2Fe(CO)(2)(PPh3)(2)] (A) as an active catalytic species. This finding was further supported by cyclic voltammetry investigations and intermediacy of an Fe(0)-Fe(II) species was established. Combined experimental and computational investigations support the existence of an iron-dihydride as the catalyst resting state, which then follows a Fe(II) based catalytic cycle to produce aldehyde.

Chiral separation of styrene oxides supported by enantiomeric tetrahedral neutral Pd(II) cages - Rajasekar, Prabhakaran; Pandey, Swechchha; Ferrara, Joseph D.; Del Campo, Mark; Le Magueres, Pierre; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2019)
The separation of enantiomers is of considerable importance in the preparation of the compounds of biological interests, catalysis, and drug development. Here, we report a novel enantioseparation of styrene epoxides (SOs) resolved in the presence of a pair of enantio-enriched tetrahedral cages. Chiral neutral cages of formula [(Pd3X*)(4)(C6O4Cl2)(6)] ([X*](3-) = RRR-or SSS-[PO(N(*CH(CH3)Ph)(3)](3)) are constructed from Pcl, building units supported by tris(imido)phosphate trianions and chloranilate linkers. These cages exhibit considerable enantioselective separation capabilities toward a series of styrene epoxides via a crystallization inclusion method. A highest enantiomeric excess (ee) value of up to 80% is achieved for the (R)-4-fluorostyrene oxide.

Refining plant oils and sugars to platform chemicals, monomers, and polymers - Pandey, Swechchha; Rajput, Bhausaheb S.; Chikkali, Samir H. (Green Chemistry, 2021)
As fossil resources continue to dwindle and environmental concerns are magnified, finding sustainable alternatives is the only way to mitigate resource availability and derisk the planet. The principles of Green Chemistry may provide guidance in this case, and renewable resources can be converted into useful platform chemicals, monomers, and polymers. This critical review examines the possibility of utilizing renewable plant oils and sugars to produce feedstock chemicals, monomers, and polymers. Among the seven isomerizing functionalization reactions of plant oils, isomerizing alkoxycarbonylation displays the highest terminal selectivity. Despite the low reactivity of sugar-derived isohexides, new strategies have been deployed to convert isohexides into difunctional monomers and polymers. The commercialization of isohexides and a few polymers derived from these building blocks has just commenced. Thus, challenges associated with isomerizing functionalization of plant oils and the use of sugar-derived isohexides in chemical syntheses have been summarized, and the potential of these renewable resources has been evaluated.

Mechanistically guided one pot synthesis of phosphine-phosphite and its implication in asymmetric hydrogenation - Sen, Anirban; Kumar, Rohit; Pandey, Swechchha; Raj, K. Vipin; Kumar, Pawan; Vanka, Kumar; Chikkali, Samir H. (European Journal of Organic Chemistry, 2022)
Although hybrid bidentate ligands are known to yield highly enantioselective products in asymmetric hydrogenation (AH), synthesis of these ligands is an arduous process. Herein, a one pot, atom-economic synthesis of a hybrid phosphine-phosphite (L1) is reported. After understanding the reactivity difference between an 0-nucleophile versus C-nucleophile, one pot synthesis of Senphos (L1) was achieved (72%). When L1 was treated with [Rh], P-31 NMR revealed bidentate coordination to Rh. Senphos, in the presence of rhodium, catalyzes the AH of Methyl-2-acetamido-3-phenylacrylate and discloses an unprecedented turn over frequency of 2289, along with excellent enantio-selectivity (92%). The generality is demonstrated by hydrogenating an array of alkenes. The AH operates under mild conditions of 1-2 bar H-2 pressure, at room temperature. The practical relevance of Ll is demonstrated by scaling-up the reaction to 1 g and by synthesizing DOPA, a drug widely employed for the treatment of Parkinson's disease. Computational insights indicate that the R isomer is preferred by 3.8 kcal/mol over the S isomer.
Keywords: asymmetric hydrogenation; catalysis; DOPA synthesis; One pot synthesis; Phosphine-phosphite ligand